KINERJA DINAS LINGKUNGAN HIDUP KABUPATEN SIAK DALAM PENGENDALIAN PENCEMARAN DAERAH ALIRAN SUNGAI (DAS) SIAK - Haryani, Endah Putri; Sudari, Mimin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Pollution found in the Siak watershed is obtained from industrial waste with a percentage of 17.01%, activities of the Department of the Environment have not been maximized so that violations exceed quality standards, and the lack of firmness in sanctioning companies is a phenomenon which was found. The purpose of this study is to find out how the performance of the Siak Regency Environmental Office in controlling pollution and to find out the inhibiting factors of the performance of the Siak Regency Environmental Agency. Control activities that have been carried out are supervision activities. This type of research is a qualitative research with a descriptive approach. Collecting data obtained both primary and secondary data collected through interviews, observations and documentation and then analyzed so that conclusions can be drawn from existing research problems. The results of this study found that the performance of the Office of the Environment in controlling pollution has not been carried out to the maximum, it is caused by several inhibiting factors namely the ability of human resources and corporate behavior. Keywords: Performance, Control, Pollution